Small scale fisheries supply chain of Lambangan village, Banggai regency: Pengaruh pemberian pupuk organik dengan jenis berbeda terhadap konsentrasi Chorella sp. secara visual - Sayuti Mohamad Sayuti Djau; Asruddin Asruddin (Fisheries and Society Publisher, 2021)
The Sustainable Development Goals (SDGs) are a global action plan that aims to end poverty, reduce inequality, and protect the environment. The success of the National SDGs is highly dependent on the success of the Village SDGs. One of the approaches taken to achieve the success of the village SDGs is through the Real Work Lecture (KKN) build village, where this program provides the broadest opportunity for the community to participate in village development facilitated by students. KKN build village program was carried out in Botumoito Village for seven weeks, from September to November 2021. The purpose of implementing this KKN build village program was to encourage the community to contribute to the development and foster a responsive attitude of the village government to the potential opportunities and problems in the village. This activity has succeeded in increasing the awareness of the people of Botumoito Village to participate in village development and has succeeded in facilitating the preparation of the Village Medium-Term Development Plan (RPJM Desa) to achieve the Village SDGs.